Pengaruh Komitmen Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Mall Of Serang - Farihah Farihah (Desanta Publisher, 2024)
The purpose of this study is to determine the effect of organizational commitment on job satisfaction and employee performance. The participants in this study were MOS Serang Banten personnel with middle management positions. The number of employees was 40 people and the sample size was 25 respondents. All data for each measurement item were tested with reliability and validity tests based on Cronbach's alpha to ensure internal consistency using the SPSS version 26 program. This study used AMOS 7 to analyze the structural equation model. Trivariate Relationship Model research shows that organizational commitment consisting of affective commitment, continuous commitment, and normative commitment has a significant positive effect on employee performance. Job satisfaction has a significant influence and mediates the effect of organizational commitment on employee performance MOS.